Real-time mask-division technique based on DMD digital lithography - Luo, Ningning; Gao, Yiqing; Chen, Min; Yu, Lixia; Ye, Qing (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Digital lithography technique is a promising tool for the fabrication of binary optical element. In this paper, we present the mask-division technique to improve the lithography quality. A piece of high-frequency mask is divided into several pieces of low-frequency binary masks. Then they are imaged on the photoresist successively by using the DMD-based lithography system. Based on the theory of partial coherent light, the intensity distribution in image plane has been simulated. The grating masks with period of 4 μm have been fabricated by using the mask-division technique. Experimental results demonstrate the feasibility of the proposed method as an effective technique for advancing the edge sharpness.
Optica Applicata, Vol. 40, 2010, nr 1, s. 239-248
Keywords: optyka; digital lithography technique; mask-division technique; DMD-based lithography; edge sharpness